ANALISIS TINGKAT KEAUSAN TERHADAP PEMAKAIAN BAN MEREK A, B DAN C MENGGUNAKAN BAN STANDAR 90/90-14 46 P - Afdan Ufriandi (Jurnal Surya Teknika, 2021)
The tire is the part of the motorbike that is in direct contact with the road surface. Selection of the correct tires, greatly determines the safety of riders from the dangers of slides on certain roads. In this research, the author aims to determine the wear rate of standard tires for Products A, B and C 90 / 90-14 M / C 46P when traveling, to prevent damage or wear of tires. In the comparison of Speeds 3,000 rpm, 3500 rpm and 4000 rpm with total load 223 Kg, 233 Kg and 243 Kg, with 1 hour in 3 times of testing. The erosion that occurs in the new tire A is 192 grams with 8.14% erosion and 7588 km / hour in tire mileage. Meanwhile, the new B tires are 182 grams, 5.71% scraping and 10,568 km / hr of the tire mileage. While the new C tire is 188 grams, 5.54% erosion and 11384 km / hour tire mileage.